Indonesian Muslim Youth Identity Construction in Indonesian Religious Films - Fadhillah Sri Meutia; Jalaluddin Jalaluddin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This paper seeks to describe the development of cultural sociology studies from a media perspective as a response to technological developments and globalization to see today's screen culture. Interestingly, it examines the encounters of American, European, Asian and Muslim cultures through Indonesian screen culture. The researcher chose the film Ayat-Ayat Cinta, as a study material because it got the attention of contemporary Indonesian Muslim audiences, making it interesting to observe. This research examines the workings of Indonesian popular religious films in shaping public opinion regarding the rise of post-Islamism by educated young Indonesian Muslims. The integration between Islam and consumption of popular culture is significantly studied in this study. Through text observation, This research finds that the relationship between religion and popular culture is not a simple cause and effect relationship. Through the perspective of semiotics and the theory of reality construction from Peter L. Berger and Thomas Luckmann, this study suggests that Indonesian Muslim youths shape themselves as subjects of modern Islam. This adjustment is modified from certain values offered by Islamic films very subtly.